COMPARATIVE ANALYSIS OF NUMERICAL METHODS FOR SOLVING ORDINARY DIFFERENTIAL EQUATIONS - Haydarova S. (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents numerical methods for solving ordinary differential equations and a comparative analysis of these methods.